Psychology - Spielman, Rose; Dumper, Kathryn; Jenkins, William; Lovett, Marilyn D. (Open textbook library., 2021)
Psychology 2e is designed to meet scope and sequence requirements for the single-semester introduction to psychology course. The book offers a comprehensive treatment of core concepts, grounded in both classic studies and current and emerging research. The text also includes coverage of the DSM-5 in examinations of psychological disorders. Psychology incorporates discussions that reflect the diversity within the discipline, as well as the diversity of cultures and communities across the globe. The second edition contains detailed updates to address comments and suggestions from users. Significant improvements and additions were made in the areas of research currency, diversity and representation, and the relevance and recency of the examples. Many concepts were expanded or clarified, particularly through the judicious addition of detail and further explanation where necessary. Finally, the authors addressed the replication issues in the psychology discipline, both in the research chapter and where appropriate throughout the book.